The Determinants that Influence Household Debt Case in Malaysia - Azwani Mohamad Azmin, N; Nabihah Wan Zaidi, W; Mohamad, Z (KnE Social Sciences, 2019)
The level of household debt in Malaysia may in turn cause another financial crisis as it is at worrying stage. Therefore, the aims of this study is to identify the relationship between household debt and its determinants as well as to determine the most significant factor that affect the household debt. The mode of empirical investigation is Ordinary Least Square Method with the multiple regressions which are applied to monthly time series data spanning from 2012 to 2016 for four variables such as Interest Rate, Inflation, Unemployment Rate and Consumption. Data collected from Eikon Thomson Reuters and Monthly Statistical Bulletin. The study implies that interest rate, unemployment rate and consumption are positive and significantly related with household debt whereas the result illustrates an insignificant yet positive relationship between inflation and household debt. As a conclusion, these findings bear important implications for Malaysian policymakers. Keywords: Interest Rate, Inflation, Unemployment Rate and Consumption.